2013
DOI: 10.1007/s10103-013-1352-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high and low level laser therapy in the treatment of Bell's palsy: A randomized double blind placebo-controlled trial

Abstract: The aim of the present study was to investigate and compare the effects of high intensity laser therapy (HILT) and low level laser therapy (LLLT) on the treatment of patients with Bell's palsy. Forty-eight patients participated in and completed this study. The mean age was 43 ± 9.8 years. They were randomly assigned into three groups: HILT group, LLLT group, and exercise group. All patients were treated with facial massage and exercises, but the HILT and LLLT groups received the respective laser therapy. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
86
0
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 29 publications
2
86
0
16
Order By: Relevance
“…Alayat and colleges reported the efficacy of laser therapy in the treatment of Bell's palsy in successive 06 weeks [8]. Fabrin and colleges concluded that acupuncture assisted electrical stimulation can reverse symptoms in short time and duration of intervention was 20 weeks , one session in one week (9).…”
Section: Discussionmentioning
confidence: 99%
“…Alayat and colleges reported the efficacy of laser therapy in the treatment of Bell's palsy in successive 06 weeks [8]. Fabrin and colleges concluded that acupuncture assisted electrical stimulation can reverse symptoms in short time and duration of intervention was 20 weeks , one session in one week (9).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A meta-analysis has reported that LILT is ineffective for the treatment of LE. 5 On the other hand, HILT has been used for a wide range of disorders, including low back pain, 14,15 knee osteoarthritis, 16 facial paralysis, 17 and subacromial impingement syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…17 Kheshie et al 16 have reported HILT and LILT combined with exercise in knee osteoarthritis were effective modalities for decreasing pain and improving the knee function scores after six weeks of treatment. In that study, HILT and exercise therapy was found to be more effective than LILT and exercise therapy, and each of them was better than placebo laser and exercise therapy in patients with knee osteoarthritis.…”
mentioning
confidence: 99%
“…Bell's palsy (BP) is represented by the paralysis of the seventh cranial nerve on one side of the face, leading to weakness of facial muscles that can result on facial expression loss causing difficulties in social relationships and loss of quality of life . BP is the most common cause of the peripheral unilateral facial nerve paralysis, being an acute, idiopathic disorder, which exact mechanism is unknown but considered to be a result of facial nerve inflammation or infection . In fact, evidences suggest that BP may be caused by reactivation of latent herpes simplex virus type 1 …”
Section: Introductionmentioning
confidence: 99%
“…The clinical symptoms of BP may include sudden onset, unilateral, weakness of the facial nerve, dry eye, an altered sense of taste, sagging of the eyelid or corner of the mouth, auricular pain, hyperacusis, and headaches . BP has an estimated annual incidence of 25 cases per 100 000, comprising 60%‐75% of cases of acute unilateral facial paralysis .…”
Section: Introductionmentioning
confidence: 99%